Amplicon Sequencing as a Potential Surveillance Tool for Complexity of Infection and Drug Resistance Markers in Plasmodium falciparum Asymptomatic Infections . (16th April 2022) - Wamae, Kevin; Kimenyi, Kelvin M; Osoti, Victor; de Laurent, Zaydah R; Ndwiga, Leonard; Kharabora, Oksana; Hathaway, Nicholas J; Bailey, Jeffrey A; Juliano, Jonathan J; Bejon, Philip; Ochola-Oyier, Lynette Isabella
Abstract: Background: Genotyping Plasmodium falciparum subpopulations in malaria infections is an important aspect of malaria molecular epidemiology to understand within-host diversity and the frequency of drug resistance markers. Methods: We characterized P. falciparum genetic diversity in asymptomatic infections and subsequent first febrile infections using amplicon sequencing (AmpSeq) of ama1 in Coastal Kenya. We also examined temporal changes in haplotype frequencies of mdr1, a drug-resistant marker. Results: We found >60% of the infections were polyclonal (complexity of infection [COI] >1) and there was a reduction in COI over time. Asymptomatic infections had a significantly higher mean COI than febrile infections based on ama1 sequences (2.7 [95% confidence interval CI, 2.65–2.77] vs 2.22 [95% CI, 2.17–2.29], respectively). Moreover, an analysis of 30 paired asymptomatic and first febrile infections revealed that many first febrile infections (91%) were due to the presence of new ama1 haplotypes. The mdr1- YY haplotype, associated with chloroquine and amodiaquine resistance, decreased over time, while the NY (wild type) and the NF (modulates response to lumefantrine) haplotypes increased. Conclusions: This study emphasizes the utility of AmpSeq in characterizing parasite diversity as it can determine relative proportions of clones and detect minority clones. The usefulness of AmpSeq in antimalarial drug resistance surveillance is also highlighted. Abstract : In this study, we highlight the utility of a multiplex amplicon sequencing panel for characterizing parasite diversity in malaria asymptomatic infections. We also emphasize the usefulness of this assay in the surveillance of antimalarial drug resistance.